Age influences post-graft-versus-host disease non-relapse mortality in adults with acute graft-versus-host disease of varying severity following allogeneic hematopoietic cell transplant. Issue 8 (3rd August 2015) - Nakane, Takahiko; Fukuda, Takahiro; Kanda, Junya; Taniguchi, Shuichi; Eto, Tetsuya; Ohashi, Kazuteru; Nakamae, Hirohisa; Kurokawa, Mineo; Mori, Takehiko; Morishima, Yasuo; Nagamura-Inoue, Tokiko; Sakamaki, Hisashi; et al.
Abstract : We retrospectively analyzed 2682 patients who developed grade II–IV acute graft-versus-host disease (GVHD). On analysis with stratification into five age groups (20–29, 30–39, 40–49, 50–59 and ≥ 60), 2-year non-relapse mortality rates (NRM) after the onset of GVHD were 20.7, 26.2, 26.6, 37.0 and 40.4%, respectively ( p < 0.001). We found a significant interaction between the patient's age and GVHD severity with respect to NRM ( p = 0.004). On multivariate analyses stratified by GVHD severity, the hazard ratio (HR) for NRM in the groups aged 50 years or more (reference: age group 20–29) was about twice as great in patients with grade II acute GVHD when compared with grade III–IV disease (HR in those aged 50–59 years: 2.9 for grade II and 1.5 [ p = 0.03 and 0.04] for grades III–IV; HR if ≥ 60 years: 3.3 for grade II and 1.5 for grades III–IV [ p < 0.001 for both]).